Population-representative study reveals cardiovascular and metabolic disease biomarkers associated with misaligned sleep schedules - Sládek, Martin; Klusáček, Jan; Hamplová, Dana; Sumová, Alena (Sleep, 2023)
STUDY OBJECTIVES: Social jetlag manifests as a difference in sleep timing on workdays and free days. Social jetlag is often associated with shorter, lower-quality sleep, so it is unclear how much the chronic circadian misalignment contributes to observed negative health outcomes. We aimed to (1) investigate associations between social jetlag, chronotype (one of its determinants), and the levels of health markers, (2) describe factors associated with social jetlag, and (3) examine whether working from home can reduce social jetlag. METHODS: Adult respondents participated in a nationally representative longitudinal survey of Czech households (individuals in each wave: n2018/19/20 = 5132/1957/1533), which included Munich ChronoType Questionnaire to evaluate chronotype and social jetlag. A subset provided blood samples (n2019 = 1957) for detection of nine biomarkers and was surveyed in three successive years (social jetlag calculated for n2018/19/20 = 3930/1601/1237). Data were analyzed by nonparametric univariate tests and mixed effects multivariate regression with social jetlag, chronotype, sex, age, body-mass index, and reported diseases as predictors and biomarker levels as outcomes. RESULTS: Higher social jetlag (≥0.65 h) was significantly associated with increased levels of total cholesterol and low-density lipoprotein cholesterol, particularly in participants older than 50 years (Mann-Whitney, men: pCHL = 0.0005, pLDL = 0.0009; women: pCHL = 0.0079, pLDL = 0.0068). Extreme chronotypes were associated with cardiovascular disease risk markers regardless of social jetlag (Kruskal-Wallis, p < 0.0001). Commuting to work and time stress were identified as important contributors to social jetlag. Individual longitudinal data showed that working from home decreased social jetlag and prolonged sleep. CONCLUSIONS: We report significant associations between sleep phase preference, social jetlag, and cardio-metabolic biomarkers.
Keywords: cirkadiánní rytmus; mužské pohlaví; Male; Surveys and Questionnaires; Humans; Female; Sleep; Jet Lag Syndrome; Metabolic Diseases; lidé; ženské pohlaví; metabolické nemoci; cholesterol; průzkumy a dotazníky; Biomarkers; biologické markery; jet lag syndrom; Circadian Rhythm; spánek; dospělí; Adult; Cholesterol